2021
DOI: 10.33019/society.v9i1.290
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Work Competency and Motivation on Employee Performance

Abstract: Employee performance has a contribution to the development of a company. The personal performance of an employee can influence by competency and work motivation factors. This research was arranged based on theoretical analysis as well as empirical studies. The research aims to define a structured thinking concept about the relationship between competency variables, work motivation, and employee performance. Worker performance is the result of efforts achieved by a person or group who work in a company. Then co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…From the discussion above, it can be stated that the findings in this research are in line with the research results of (Azhariansyah, et al, 2021) stated that positive motivation influences employee performance. Similar results were also found by (Dewi, 2018;Gede & Piartini, 2018;Inando, 2021) and (Darmawan & Tanuwijaya, 2023) who stated that motivation has an effect on increasing employee performance.…”
Section: The Influence Of Work Motivation On Employee Performancesupporting
confidence: 83%
“…From the discussion above, it can be stated that the findings in this research are in line with the research results of (Azhariansyah, et al, 2021) stated that positive motivation influences employee performance. Similar results were also found by (Dewi, 2018;Gede & Piartini, 2018;Inando, 2021) and (Darmawan & Tanuwijaya, 2023) who stated that motivation has an effect on increasing employee performance.…”
Section: The Influence Of Work Motivation On Employee Performancesupporting
confidence: 83%
“…Motivation is the driving force that causes and directs an employee's behavior (Wijayanto and Riani, 2021;Margahana et al, 2018); Nurcahyani and Adyani, 2016). (Singh, 2011) defines motivation as the force that compels a person to strive for excellence.…”
Section: H1: Discipline Influences Job Satisfactionmentioning
confidence: 99%
“…Like at i3L, in education in other case studies, a positive and significant effect between competency and Performance has also been found (Qurtubi, 2023). Even in more extensive cases, competency leads to a deep and ingrained employee personality that directly improves Performance (Wijayanto & Riani, 2021). The importance of competency in improving employee performance is indeed reflected in research conducted by (Mullins John, 1996), where competency has been found to assist a company in growing in the face of an uncertain market through responsive employee performance.…”
Section: The Effect Of Career Development On Employee Performance At I3lmentioning
confidence: 99%